The Impact On The Growth Of The Textile Industry In Malaysia After China Entered Into World Trade Organization (WTO) - Ling, Chin Pei (2004)
By knowing the positive and negative impacts on China's accession into WTO, we will be able to take charge of our own nation. The accession will basically result in changes to all nations in the world by forcing the industry to open the market to new entrants. However, opportunity will be created with this and along the way there must be some drawbacks as it will be threat to the local producers as well.